Artificial Intelligence Adoption and Generation Z Work Adaptation - Sidjabat, Sonya; Tjiwidjaja, Halim; Ramdhan, Muhammad; Sutariyono, Sutariyono (Journal of Business Management and Economic Development, 2026)
The rapid development of artificial intelligence (AI) has significantly transformed workplace practices and employee work patterns. This study aims to analyze the relationship between AI adoption and Generation Z work adaptation in workplaces in Cianjur Regency. The research focuses on how AI implementation influences employee adaptation, organizational support, digital work culture, and work performance. A quantitative research approach was employed using survey data collected from Generation Z employees working in various organizations in Cianjur Regency. The data were analyzed using statistical techniques to examine the relationship between AI adoption, work adaptation, and employee performance. The findings indicate that Generation Z employees demonstrate a high level of adaptability to AI-based work environments due to their familiarity with digital technologies and openness to technological innovation. AI adoption was found to enhance work efficiency, facilitate information processing, and support data-driven decision-making. In addition, organizational support and a supportive digital work culture play an important role in strengthening employees’ ability to integrate AI tools into their daily work activities. The study also reveals that AI adoption positively influences employee work performance and contributes to improved productivity and workplace effectiveness. These findings highlight the importance of strengthening digital competencies and organizational support systems to optimize AI implementation and support sustainable workforce development in regional workplaces.